Viewing the Afro-Mexican Female Revolutionary: Francisco Rojas González's La negra Angustias - Kanost, Laura (My University, 2017)
Francisco Rojas González's 1944 novel La negra Angustias is recognized as the only novel of the Mexican Revolution that features a black woman military officer. Critics have observed that, although this semi-biographical novel portrays Angustias as a gender nonconformist who seeks justice for women and the poor, the conclusion ushers her firmly back to her expected place in society as she falls in love and becomes a self-sacrificing wife and mother. I argue that this apparent reversal is present throughout the novel in a narrative gaze that objectifies Angustias, ogling her brown, curvy body. Furthermore, Angustias herself appropriates the power of the gaze and orchestrates striking visual performances at key points in her trajectory. Thus, the novel foregrounds multiple relationships of viewer and viewed, as Rojas oscillates between rewriting and reiterating nationalist discourses, celebrating and negating the agency of his protagonist.
Citation: "Viewing the Afro-Mexican Female Revolutionary: Francisco Rojas González’s La negra Angustias." Hispania 93.4 (2010): 555–562.
Keywords: Afro-Mexicans; Francisco Rojas González; Gender; La negra Angustias; Narrative Gaze; novel of the Mexican Revolution,